Patellar Dislocation in the United States: Role of Sex, Age, Race, and Athletic Participation - Waterman, Brian R.; Belmont, Philip J.; Owens, Brett D. (The Journal of Knee Surgery, 2012)
Patellar instability has been extensively studied in selected, high-risk cohorts, but the epidemiology in the general population remains unclear. A longitudinal, prospective epidemiological database was used to determine the incidence and demographic risk factors for patellar dislocations presenting to emergency departments of the United States. The National Electronic Injury Surveillance System was queried for all patellar dislocations presenting to emergency departments between 2003 and 2008. Incidence rate ratios (IRRs) were then calculated with respect to sex, age, and race. The hypothesis was that patellar dislocation is influenced by sex, age, race, and athletic participation. An estimated 40,544 patellar dislocations occurred among an at-risk population of 1,774,210,081 person-years for an incidence rate of 2.29 per 100,000 person-years in the United States. When compared with males, females showed no significant overall or age-stratified differences in the rates of patellar dislocation (IRR 0.85, 95% CI 0.71, 1.00; p = 0.08; p > 0.05). Peak incidence of patellar dislocation occurred between 15 and 19 years of age (11.19/100,000 person-years). When compared with Hispanic race, black and white race were associated with significantly higher rates of patellar dislocation (IRR 4.30 [95% CI 1.63, 6.97; p = 0.02], IRR 4.02 [95% CI 1.06, 6.98; p = 0.03], respectively). Nearly half (51.9%) of all patellar dislocation occurred during athletic activity, with basketball (18.2%), soccer (6.9%), and football (6.3%) associated with the highest percentage of patellar dislocation during athletics. Age between 15 and 19 years is associated with higher rates of patellar dislocation. Sex is not a significant risk factor for patellar dislocation. Black and white race are a significant risk factor for patellar dislocation when compared with Hispanic race. Half of all patellar dislocation occurs during athletic activity. This study was conducted on the Level of evidence II.
Keywords: patella; dislocation; patellofemoral; instability; epidemiology